On Appeals to Nature and their Use in the Public Controversy over Genetically Modified Organisms - Moldovan, Andrei (Informal Logic, 2018)
In this paper I discuss appeals to nature, a particular kind of argument that has received little attention in argumentation theory. After a quick review of the existing literature, I focus on the use of such arguments in the public controversy over the acceptabil-ity of genetically-modified organisms in the food industry. Those who reject this biotechnology invoke its unnatural character. Such arguments have re-ceived attention in bioethics, where they have been analyzed by distinguishing different meanings that “nature” and “natural” might have. I argue that in many such appeals to nature the main deficiency of these arguments is semantic, in particular, that these words cannot be assigned a determi-nate meaning at all. In doing so, I rely on semantic externalism, a widely accepted theory of linguistic meaning.